2021
DOI: 10.1038/s41467-021-21324-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically robust amino acid crystals as fiber-optic transducers and wide bandpass filters for optical communication in the near-infrared

Abstract: Organic crystals are emerging as mechanically compliant, light-weight and chemically versatile alternatives to the commonly used silica and polymer waveguides. However, the previously reported organic crystals were shown to be able to transmit visible light, whereas actual implementation in telecommunication devices requires transparency in the near-infrared spectral range. Here we demonstrate that single crystals of the amino acid L-threonine could be used as optical waveguides and filters with high mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 73 publications
1
75
0
1
Order By: Relevance
“…The above phenomenon showed that the crystal had the nature of multi-faceted bending and exhibited good mechanical properties, which had the potential application in fiber-optic transducers, mechanical deformation-induced discoloration materials, waveguiding biomaterials, artificial muscles, etc. [42][43][44][45] In order to further study the surface morphology and face index of the crystal, we selected a crystal and conducted a SEM test. As shown in Figure S3, the crystal surface had defects and was not completely smooth.…”
Section: Resultsmentioning
confidence: 99%
“…The above phenomenon showed that the crystal had the nature of multi-faceted bending and exhibited good mechanical properties, which had the potential application in fiber-optic transducers, mechanical deformation-induced discoloration materials, waveguiding biomaterials, artificial muscles, etc. [42][43][44][45] In order to further study the surface morphology and face index of the crystal, we selected a crystal and conducted a SEM test. As shown in Figure S3, the crystal surface had defects and was not completely smooth.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, optical waveguide properties of organic crystals focus on the visible light region, while very limited information exists in the near‐infrared [54, 55] . Therefore, the optical waveguiding properties of form A and B crystals of BPEA were assessed in the O band (1260–1360 nm) and the C band (1530–1565 nm) by coupling a single crystal with a near‐infrared input light from tunable laser sources.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, organic semiconducting crystals have not been explored yet as multifunctional devices with broadband photodetection (visible and near‐infrared) and optical transduction in the near‐infrared region. However, photodetecting capability and optical transduction performance in the telecommunications (datacom) range (1250–1600 nm) is germane to the development of multifunctional optoelectronic single crystal devices [55] . Our own investigation of this material showed that crystals of the two phases have diametrically different mechanical properties; while crystals of form A are elastic at room temperature, crystals of form B are brittle but become plastic at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the dioxanebased system, (trans-azo)(pyrazine) showed a differential response to irradiation by different laser power (Supplementary Figs. [33][34][35]. Irradiating a crystal of ~15 μm thickness at 5 mW for 40 ms produced no response, while irradiating with a pulse of the same length but at a power of 15 mW led to fog emission.…”
Section: Cocrystal Laser Micro-shaping Of (Trans-azo)(pyrazine)mentioning
confidence: 99%
“…isomerization, 22,23 dimerization, 24,25 or polymerization 26,27 ); photomechanical motion, 21,[28][29][30] photochromism, 31 and waveguide behaviour. 32,33 While traditional photolithography has been applied to polymeric resins, 34 hyperbolic metamaterials, 35 nanostructures, 36 photonic crystals 37 and cocrystal thin films, 38 the ability to accurately shape, or machine, organic crystalline solids using low-powered visible or ultraviolet (UV) light has yet to be achieved. While machining of patterns has been reported using high-energy beam techniques, such as focused ion beam (FIB) milling, 39 electron beam lithography, or femtosecond laser beam machining, 40 these methods operate at high energies (1-50 keV) and beam powers (on the order of several Watts) that produce chemical damage to organic materials, and are most commonly used for organic polymers and inorganic materials.…”
mentioning
confidence: 99%